Above the Clavicle: A Simplified Screening Method for Asymptomatic Blunt Cerebral Vascular Injury. Issue 1 (January 2023) - McCullough, Mary A.; Cairns, Ashley L.; Shin, Jaewook; Appelbaum, Rachel D.; Couture, Daniel E.; Nunn, Andrew M.; Miller, Preston R.; Martin, Robert S.; Carmichael, Samuel P.
Introduction: Blunt cerebrovascular injury (BCVI) is an increasingly detected pattern in trauma with significant morbidity, putting patients at risk for subsequent stoke. Complex screening protocols exist to determine who should undergo CT angiography of the neck (CTAN) to evaluate for BCVI. Once identified, stroke incidence may be reduced with appropriate treatment across grades. We hypothesize that an expanded and simplified method for identifying patients with clinical suspicion for BCVI based upon injury above the clavicle (ATC) will illustrate a previously undiagnosed cohort of patients. Methods: A single-institution retrospective review of adult (age ≥18 years) blunt trauma patients with BCVI from January 1, 2010 to December 31, 2019 was conducted at a tertiary academic medical center. Patients undergoing CTAN were divided into 2 groups based upon qualification by either the expanded Denver criteria or clinical evidence of any injury ATC. Results: A total of 219 patients were diagnosed with BCVI (25 566 blunt trauma admissions, .9% incidence). Seventeen patients (8%) who did not satisfy expanded Denver were diagnosed with BCVI by ATC, most commonly undergoing CTAN due to facial trauma (n = 8). There were no differences in distribution of carotid artery injuries (CAI) and vertebral artery injuries (VAI) in the expanded Denver criteria group compared to the ATC group. Conclusions: CTAN for blunt trauma with any injury ATC is an easy-to-use screening tool and may be seamlessly included with initial whole-body imaging.